A produção textual em comunicação social: uma proposta multimodal - Oliveira, Eneida Martins de (2009)
The purpose of this research is to investigate multimodal literacy in media genres considering a didactic proposal to reading and text production with students from Undergraduate Social Communication Course. The targets are: 1) To develop practices of multimodal literacy through textual production with students from Undergraduate Social Communication Course (Journalism and Broadcast); 2) To build up students perception of multimodality in media genres such as: news, chronicles among other media genres, etc.); 3) to develop reading practices and significant writing skills of multimodal texts in classroom, which is based on Schneuwly and Dolz s proposals (2004); 4) to evaluate the multimodal literacy process taking in consideration the reading and writing practices developed throughout the research as well as the texts produced by the students. We explored the process of textual production with students from the above mentioned course, thus promoting the multimodal literacy of the text producer, based on work with didactic sequences as proposed by Schnewly & Dolz (2004).The theoretical framework draws on literacy and modality explored by MARCUSCHI (2005), SOARES (2004), KLEIMAN (1995/2005); KRESS e van LEEUWEN (1996), DIONÍSIO (2005), VIEIRA (2007), ALMEIDA (2008). The methodological perspective is based on SCHNEWLY & DOLZ (2004) proposals. We discussed aspects about textual genre following MARCUSCHI (2005), KLEIMANN (1995/2005) described the whole textual production. The analysis of the texts produced by the 16 selected students following the didactic sequence proposed showed peculiarities in the process of text elaboration such as student s resistance to rewrite, a marginal practice in the literacy history of subject/authors. The texts were in line with the genre chosen by the producer, with textual factors, for they were cohesive, coherent and evidenced the authorship marks. In some of them there occurred intertextuality using other known texts. Considering the concept of multimodality, the texts make it visible the level of literacy of text producers, responding to the language function as well as to composition principles proposed by KRESS & van LEEUWEN (1996) and explored in this analysis. Finally, we emphasized the contribution of the theory and its applicability to the multimodal textual production, as well as to that which does not fit the theory, neither to this production. For example, the related questions to given and new: the information value of left and write, center and margin, the colors importance of colors, pointing to possible changes which contribute to the multimodal textual production process in Higher Education.